Validity of a soccer defending skill scale (SDDS) using game performances - Suzuki, K.; Nishijima, T. (International Journal of Sport & Health Science, 2004)
The purpose of this study was to examine the validity of a soccer defending skill scale (SDSS) measured by the ocation of players in soccer games using structural equation modeling. The samples were 469 defending performances in the final of FIFA World Cup Korea / Japan 2002TM (Brazil vs. Germany), which were determined by distances, and angles, between attackers and defenders, and the number of players. Results for the general CFA model consisting of the selected 9 items indicated a good fi t to the data (CFI= .994, RMSEA=.032). The causal structure model of the defending skills was statistically valid (CFI= .991, RMSEA= .037). The multidimensional CFA model indicated a much better fit to the data than the general CFA model (?2 = 17.378 with 8 df, p < .05). It was concluded that the SDSS with 9 items successfully was able to measure the game performance according to the causal structure of the tactical defending phase, and the SDSS was able to measure multi-dimensional abilities consisting of the defending phase and the defending object.